Son [videorecording (DVD)] - Kavanagh, Ivan; Kavanagh, Ivan; Matichak, Andi, 1994-; Hirsch, Emile, 1985-; Blumm, Luke David (RLJE Films, 2021)
After intruders linked to a cult from her past try to steal her son, a woman notices that her son has developed a mysterious illness and she tries desperate measures to keep him alive.